The influence of stellar wind bubbles on the ionizing radiation field in HII regions - Koshmak, I.O.; Melekh, B.Ya. (Advances in Astronomy and Space Physics, 2012)
Stellar wind around starbursts forms cavities filled by hot gas with low density, thermalized by inverse wind shock. Young starbursts can contain the compact cavities inside Hii region. Diffuse ionizing radiation, that arises in the cavity could considerably affect the medium ionization. Outside the stellar wind bubble a thin dense shell formed by the direct wind shock is located. This shell can appreciably transform the shape of the ionizing radiation spectrum in neighbouring region. We investigate this possibility, using the density and temperature distributions of density and temperature, and other physical parameters of bubble-like structures given by Weaver et al. (1977).